Alloreactive natural killer cells in targeting high-risk leukaemias. (20th November 2008) - Moretta, L; Locatelli, F; Moretta, A
Abstract : Natural killer (NK) cells express surface receptors that regulate potent effector functions, such as cytolytic activity and release of cytokines, which play a central role in inflammatory response and immunoregulation. In this paper, major advances are outlined from the original discovery of HLA-class I-specific inhibitory receptors in humans to recent, particularly successful, clinical applications in the cure of high-risk, otherwise fatal leukaemias. The central role of donor-derived "alloreactive" NK cells in eradicating leukaemic cells in the T-cell-depleted haploidentical haematopoietic stem cell transplantation setting became evident. Since alloreactive NK cells seem to play a key role also in preventing graft rejection and graft-vs-host disease, they may be an ideal tool to treat high-risk leukaemias in the haematopoietic stem cell transplantation setting.